2018
DOI: 10.24326/asphc.2018.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value and Mineral Concentrations of Sweet Basil Under Organic Compared to Chemical Fertilization

Abstract: Safe production of leafy vegetables is more important than other horticultural crops due to their significant contribution in health promotion of consumers. In present study, the growth and nutritional quality of sweet basil plants (Ocimum basilicum L.) were evaluated under some organic compared to chemical NPK fertilizing treatments. A non cultivated soil was used in the experiment, and treatments were arranged in completely randomized design with four replications. Manure in 20 and 40% of pot volume, vermico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 11 publications
6
28
2
Order By: Relevance
“…This research work supports the findings of [ 43 , 44 ] that integrated nutrient application gave higher crop yield compared with the recommended sole inorganic and organic fertilizers. The authors also reported that an integrated application of organic and inorganic fertilizer would build up soil productivity and quality on a long-term basis.…”
Section: Discussionsupporting
confidence: 90%
“…This research work supports the findings of [ 43 , 44 ] that integrated nutrient application gave higher crop yield compared with the recommended sole inorganic and organic fertilizers. The authors also reported that an integrated application of organic and inorganic fertilizer would build up soil productivity and quality on a long-term basis.…”
Section: Discussionsupporting
confidence: 90%
“…Besides nitrogen, plants use five other nutrients in relatively large amounts: phosphorus, potassium, sulphur, calcium and magnesium [61]. In terms of phosphorus and potassium content, the results showed medium values ranging between cow manure and vermicompost, as used by Naiji and Souri [62] in their investigation. Table 6.…”
Section: Use Of Biochars Mixed With Compostmentioning
confidence: 99%
“…Similarly, separate individual application of P fertilizer at the rate of 46 kg P 2 O 5 ha −1 resulted in average soil N content of 29.2 kg ha −1 . It is a fact that under poor soil conditions, application of N and P fertilizers at small rates can increase plant root growth and development, as well as BNF efficiency ( Pourranjbari Saghaiesh et al., 2019 ; Aslani and Souri, 2018 ; Naiji and Souri, 2018 ). Our results indicated that with the application of starter N and P fertilizers residual soil N is enhanced after harvesting of groundnut.…”
Section: Resultsmentioning
confidence: 99%